PENERAPAN ARTIFICIAL INTELLIGENCE (AI) UNTUK MENINGKATKAN STRATEGI PENJUALAN DAN PEMASARAN PADA UMKM CINDUR BATIK BATAM - Friadi, John; Windayati, Diana Titik; Kurniawati, Ely; Ahmad Fuad; Nur Andini Rianti (Universitas Andi Djemma, 2025)
Empowering MSMEs is a strategic key in optimizing local economic. Challenge faced MSME in increasing competitiveness typically related to ineffective sales and marketing approaches, inadequate active customer service, and a lack of digital knowledge among MSME members. Artificial Intelligence (AI) is a rapidly developing technology and is applied in various fields, including sales and marketing. This community service activity aims to understand the use of AI technology in collecting, analyzing, and utilizing customer data to generate information about customer behavior, sales and marketing, and potentially profitable market trends especially in MSMEs. The method includes preparation stages, surveys, development of an AI-based e-commerce platform, training in the implementation of the platform, and monitoring and evaluation of the overall implementation of the service. This activity was carried out to increase the insight of Cindur Batik MSME in optimizing product sales and marketing strategies to increase competitiveness and address global economic challenges. The result of this activity was the development of an AI-based e-commerce platform, which is used to increase marketing and sales at Cindur Batik MSME Batam. Based on this application, MSMEs partner have an understanding of the use of AI in creating image and video content for digital marketing.